The GAFa domain of phosphodiesterase-6 contains a rod outer segment localization signal - Cheguru, Pallavi (2013)
Phosphodiesterase – 6 (PDE6) is a peripheral membrane protein synthesized in the inner segment of photoreceptor cells. Newly synthesized PDE6 is transported to the outer segment (OS) where it serves as a key effector enzyme in the phototransduction cascade. Proper localization of PDE6 in photoreceptors is critically important to the function and survival of photoreceptor cells. The mechanism of PDE6 transport to the OS is largely unknown. In this study, we investigated potential OS targeting signals of PDE6 by constructing PDE5/PDE6 chimeric and mutant proteins and analyzing their localization in rods of transgenic Xenopus laevis. We found that efficient OS localization of chimeric isoprenylated PDE enzymes required the presence of a targeting motif within the PDE6 GAFa domain. Furthermore, the GAFa-dependent localization signal was sufficient to target EGFP-GAFa fusion protein to the OS. Our results support the idea that effective trafficking of the peripheral membrane proteins to the OS of photoreceptor cells requires a sorting/targeting motif in addition to a membrane-binding signal.